Parks and recreation. Season four [videorecording (DVD)] - Daniels, Greg (Universal Studios Home Entertainment, 2012)
In this comedy, Leslie Knope (Amy Poehler) is an ever-enthusiastic government employee who has her sights set on the City Council. Features all 22 episodes.